The Implementation of CHSE in Front Office Departement at The Apurva Kempinski Bali - I Gede Eka Suryawan; Ni Ketut Bagiastuti; I Ketut Suarja; Made Sudiarta (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: This study aims to determine the model and impact of the implementation of CHSE at The Apurva Kempinski Bali, especially in the front office department. Research methods: The study uses qualitative techniques with 5 approach models. The types of data used in this research are qualitative and quantitative. The method of data collection in this research is carried out by several stages, namely observation, interview, documentation, and literature research. Results and discussion: The results of the study are the front office department at The Apurva Kempinski has 3 models of implementations CHSE. The 3 model CHSE implementation are model implementation provided by hotel, model implementation done by hotel guest, and model implementation done by cast and crew front office departement. Implication: The implementation of CHSE at The Apurva Kempinski Bali received positive comments from guests. Keywords:: protocol of healty, CHSE, front Office, Covid-19.